The Effectiveness of Using the Socrative Application on the Indonesian Language Learning Outcomes of Grade X Students at UPT SMA Negeri 4 Sidrap - Asriana Asriana; Usman M; Hasanuddin Hasanuddin (Universitas Muhammadiyah Enrekang, 2025)
This study employed a quantitative approach with a quasi-experimental method and a Posttest Only Control Group Design. The research population consisted of all 74 tenth-grade students of UPT SMA Negeri 4 Sidrap, and the sampling technique used was total sampling, thereby including the entire population as the sample. The research instruments were a 20-item multiple-choice objective test and a questionnaire. The results showed that the average posttest score of the experimental group using the Socrative application was 84.72, while the control group using conventional tests obtained an average score of 54.72. Thus, the use of the Socrative application proved effective in improving the Indonesian language learning outcomes of the tenth-grade students at UPT SMA Negeri 4 Sidrap.